2009
DOI: 10.1002/mnfr.200800563
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined action of pancreatic lipase and pancreatic lipase‐related proteins 1 and 2 on native versus homogenized milk fat globules

Abstract: Pancreatic lipase (PL) and pancreatic lipase-related proteins 1 and 2 (PLRP1 and PLRP2) display different functional properties, despite close structures. The aim of the study was to compare the kinetic properties of recombinant human PLRP1, PLRP2, and PL on a physiological substrate: the milk fat under native and homogenized structures. No lipolytic activity is measured for PLRP1. PLRP2 hydrolyses milk fat with a lower catalytic efficiency than that of PL. PLRP2 activity, higher on homogenized than on native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 46 publications
(90 reference statements)
3
36
0
1
Order By: Relevance
“…A similar synergistic effect was recently shown for PLRP2 and PTL when digesting TG presented as bovine milk fat globules ( 33 ) and for PTL and PLRP2 when digesting RE ( 29 ). The molecular or physical-chemical explanation behind these synergisms are presently not understood; however, a synergistic effect between PLRP2 and BSSL should be important in neonatal lipid digestion as the capacity to digest fat is often a limiting factor in energy utilization, particularly when it is from infant formula or pasteurized human milk, as neither contains active BSSL ( 18 ).…”
Section: Discussionsupporting
confidence: 83%
“…A similar synergistic effect was recently shown for PLRP2 and PTL when digesting TG presented as bovine milk fat globules ( 33 ) and for PTL and PLRP2 when digesting RE ( 29 ). The molecular or physical-chemical explanation behind these synergisms are presently not understood; however, a synergistic effect between PLRP2 and BSSL should be important in neonatal lipid digestion as the capacity to digest fat is often a limiting factor in energy utilization, particularly when it is from infant formula or pasteurized human milk, as neither contains active BSSL ( 18 ).…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, Berton et al reported a similar lag phase for hydrolysis of triglycerides in raw, non-homogenised cow's milk by human pancreatic lipase [61]. Structurally, breast milk fat globules differ from those of infant formula.…”
Section: Resultsmentioning
confidence: 93%
“…Phospholipids Galactolipids Esters of vitamin A Berton & al., 2009Thirstrup & al., 1994Sias & al., 2004Reboul & al., 2006 Carboxyl ester lipase Verheij & al., 1983 Abbreviations: HPL, human pancreatic lipase; TG, triglycerides Table 2. Human pancreatic enzymes involved in lipid digestion…”
Section: Enzyme Name Substrate Specificity Referencesmentioning
confidence: 99%
“…The pancreatic lipase-related 2 protein (hPLRP2), with a broader substrate specificity, hydrolyzes milk triglycerides (Berton & al., 2009) phospholipids (Jayne & al., 2002;Lowe, 2002;Thirstrup & al., 1994) galactolipids (Sias & al., 2004) and esters of lipid-soluble vitamins (Reboul & al., 2006). Carboxyl ester lipase (also called bile salt-stimulated lipase, On a weight basis, the ratio of pancreatic lipase to gastric lipase total secretory outputs was found to be around four after 3 hours of digestion.…”
Section: Human Dietary Lipid Digestion Process and Regulation Of Pancmentioning
confidence: 99%